2016
DOI: 10.1093/eurheartj/ehw047
|View full text |Cite
|
Sign up to set email alerts
|

Transcoronary gradients of vascular miRNAs and coronary atherosclerotic plaque characteristics

Abstract: The overall plaque burden and plaque phenotypes are associated with changes in the kinetics of miR-concentrations across the transcoronary passage. Transcoronary gradients of the anti-atherosclerotic miR-126-3p and miR-145-5p correlated with the extent of TCFAs, suggesting that instable plaques may affect the local uptake or degradation of these miRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 40 publications
3
45
0
1
Order By: Relevance
“…A pilot study also demonstrated a potential feasibility of serum miR-126 as a marker of acute MI [105]. Recently, Leistner et al [108] obtained interesting results suggesting for a significant value of transcoronary gradients of miR-126 in prediction of the presence of rupture-prone plaques.…”
Section: Mir-126 and Atherosclerosismentioning
confidence: 89%
See 1 more Smart Citation
“…A pilot study also demonstrated a potential feasibility of serum miR-126 as a marker of acute MI [105]. Recently, Leistner et al [108] obtained interesting results suggesting for a significant value of transcoronary gradients of miR-126 in prediction of the presence of rupture-prone plaques.…”
Section: Mir-126 and Atherosclerosismentioning
confidence: 89%
“…In cardiovascular pathology, circulating miR-126 concentrations are markedly reduced and negatively correlate with pathological determinants. The diagnostic and prognostic value of circulating miR-126 as a molecular marker of ischemic stroke, biomarker of severity of atrial fibrillation and heart failure, and predictor of adverse cardiovascular events in heart failure was shown in several studies [102][103][104][105][106][107][108][109] (Table 1). A pilot study also demonstrated a potential feasibility of serum miR-126 as a marker of acute MI [105].…”
Section: Mir-126 and Atherosclerosismentioning
confidence: 99%
“…A recent study showed that patients with CAD have lower circulating levels of miR-126, likely playing a role in plaque instability. 47 In PAH, miR-126 was also described as an important player of endothelial integrity and its downregulation in patients with PAH led to decreased vascular density in the RV 33 and peripheral muscle. 32 Thus, these epigenetic alterations may also increase the susceptibility of patients with PAH to develop CAD.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs with high myocardial expression (i.e. myomiRs, see above) are increased in peripheral blood of patients with AMI [81,82]. To evaluate the usefulness of miRNA quantification for AMI diagnostic purposes, their comparison with established biomarkers, such as cardiac troponins (cT), is essential.…”
Section: Diagnostic Biomarkers Single Mirnas In the Diagnosis Of Acutmentioning
confidence: 99%